SYSTEM OF PSYCHOTHERAPY TO FAMILY MALADJUSTMENT FOR MEN AND WOMEN WITH PERSONALITY DISORDERS - Kurilo V.А.; Danilevskaya, N.V. (World of Medicine and Biology, 2012)
Developed and clinically tested system of psychotherapy, and family maladjustment prevention for patients with personality disorders. The developed system consists of six stages in which the individual applied methods of psychotherapy, family psychotherapy, group psychotherapy, including psychoanalytically oriented psychotherapy, hypnotherapy, cognitive-behavioral therapy, personality-oriented, reconstructive, self-hypnosis, etc. The study proved the effectiveness of the developed system of psychotherapy and secondary prevention.В результате проведенного исследования доказана эффективность разработанной системы психотерапии и вторичной профилактики.